KEBIJAKAN HUKUM PENGENAAN SANKSI TINDAKAN BERUPA PROGRAM LATIHAN KERJA BAGI ORANG TUA YANG MENGEKSPLOITASI ANAK DALAM PEMBAHARUAN HUKUM PIDANA INDONESIA - Ade Mulyani; Erdianto Effendi; Ferawati Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
In the explanation of Article 76I of the Child Protection Act, it is explainedthat everyone is prohibited from placing, allowing, doing, ordering to do orparticipate in economic and/or sexual exploitation. However, until now variouskinds of problems regarding child protection are still difficult to handle, sanctionsagainst parents or anyone who exploits children, both economically and/orsexually, is a maximum imprisonment of 10 years and/or a maximum fine of Rp.200 million. However, to determine criminal sanctions often cannot be applied bythe authorities for several reasons. One of them is a dilemma by the police whoare in charge of arresting the perpetrators, in cases of child exploitation becauseparents are forced to send their children to work to help them make ends meet.The main problems in this research are: How is the regulation related to childexploitation in Indonesia's current positive law; How is the effectiveness of thelegal policy regulating the imposition of sanctions for acts of exploitation ofchildren by parents in the renewal of Indonesian criminal law.The type of research used in this research is normative legal research or itcan also be called doctrinal legal research. Normative legal research is librarylaw research. This research focuses on legal principles. The legal principle usedis the principle of expediency.In connection with the application of sanctions for perpetrators of childexploitation, both economically and sexually as mentioned above, the authors didnot find a solution to the imposition of criminal sanctions and fines. This isbecause criminal sanctions and fines do not deter perpetrators, but it becomeseven more difficult when it is seen again that the factor that causes them to exploitis the absence of proper work, which is able to provide for their lives. If there areother sanctions that can provide pre-employment guidance, then the number ofcases of child exploitation will decrease because in this case the perpetratorshave received briefings to continue work in accordance with their respectiveskills. There needs to be special rules and their solutions that discuss theexploitation of children who are used by parents, especially economically. It ishoped that there will be action sanctions in applying sanctions in cases of childexploitation, in the form of a training with self-reliance development with severalJOM Fakultas Hukum Univ Riau Vol. IX Edisi 2 Juli - Desember 2022 Page 2programs such as skills to support independent businesses, which are realized inthe form of handicrafts, industry and households.Keywords: Child Exploitation - Parents - Action Sanctions.